Impact of different levels of low-fat dried distillers grains in finishing diets on performance, nutrient intake and digestibility, in situ degradability and on protein and energy intake and retention and estimation of protein and energy requirements of young Nellore bulls - Alhadas, Herlon Meneguelli (2022)
This study was developed in two experiments, one with performance animals and the other with cannulated animals. Each of the two experiments originated two chapters of this thesis, totaling four chapters. In the first chapter, the effect of including low-fat dried distillers grains (DDG) on young Nellore bulls performance, nutritional parameters and nitrogen metabolism was evaluated. Thirty-five Nellore cattle were randomly divided into four diets: without DDG (D0) or with the inclusion of DDG at 150 g/kg (D150), 300 g/kg (D300), or 450 g/kg (D450). The evaluation period lasted 126 days and three periods of collection of feces and urine were carried out. Final body weight (P = 0.099) and average daily gain (P = 0.097) tended to decrease linearly; the digestibility of dry matter (DM, P < 0.001), organic matter (OM, P < 0.001), ether extract (EE, P < 0.001) and non-fiber carbohydrates (NFC, P < 0.001), and intakes of total digestible nutrients (TDN, P < 0.001) decreased linearly. The increase in crude protein intake (CP, P < 0.001) did not result in an increase in the amount of nitrogen retained (N, P = 0.540). In the second chapter, the effect of including low-fat DDG in finishing diets on protein and energy intake and retention and to estimate the protein and energy requirement of young Nellore bulls was evaluated. Thirty-five animals were used: baseline (n = 4), maintenance (n = 4), and ad libitum intake (n = 27). Ad libitum animals were divided into four groups: diets with the inclusion of DDG at the levels of 0, 150, 300 and 450 g/kg (DM basis). At the end of the experiment all animals were slaughtered. There was a linear reduction with increasing DDG levels in the TDN (P = 0.008), metabolizable energy (ME) intake (P < 0.010), in total retained energy (P = 0.065), and in heat production (P < 0.065). Metabolizable protein (MP) intake increased linearly (P < 0.010), but retained protein did not differ (P = 0.499). Daily net energy and ME requirement for maintenance was 75.9 and 122 kcal/kg 0.75 EBW, respectively. Daily MP for maintenance was 3.6 g/kg 0.75 shrunk body weight. In the third chapter it was evaluated the effect of including levels of low-fat DDG in high-concentrate diets on intake and digestibility. Four rumen-cannulated Nellore cattle received four dietary treatments in a 4×4 Latin square experimental design. Treatments included diets without DDG (D0) and varying inclusion levels of DDG at 150 g/kg (D150), 300 g/kg (D300), and 450 g/kg (D450). Four periods of total feces and urine collection were performed to estimate nutrient intake and digestibility and estimate nitrogen balance. Collections of omasum digesta were used to estimate ruminal degradability. The ruminal emptying technique was performed to estimate the ruminal rates of ingestion, passage, and digestion (kd). The inclusion of DDG reduced the intake of TDN (P < 0.010), DM (P = 0.020), OM (P = 0.020), NFC (P < 0.010) and EE (P = 0.060). The intake of neutral detergent fiber (NDF) increased linearly (P < 0.01), whereas CP had a quadratic pattern (P = 0.020). The total digestibility in kg/d of DM (P < 0.010), OM (P < 0.010), NFC (P < 0.010) and EE (P = 0.020) decreased linearly. The total digestibility in kg/d of the NDF increased linearly (P < 0.010) and the CP had a quadratic pattern (P = 0.010). The kd of DM (P = 0.010), OM (P < 0.010) decreased linearly and NDF increased linearly (P < 0.010). The amount of N retained did not change (P = 0.720), but the intake of MP increased (P = 0.03). And in the fourth chapter, it was evaluated ruminal in situ degradation of diets containing different levels of DDG replacing soybean meal, urea and corn and the effect of these diets on in situ ruminal degradation of DDG, and to propose alternative methods to estimate in vivo digestibility of diets. Four rumen-cannulated Nellore bulls were used in a 4×4 Latin square design, for both in situ incubation and in vivo digestibility. We evaluated the following treatments: diet without DDG (D0) or containing 150 (D150), 300 (D300), or 450 g/kg (D450) of inclusion. For in situ evaluation, DDG was incubated in all animals, and diets only in those fed with the same diet that would be incubated. To estimate in vivo digestibility, three days of total feces collection were performed in each period. Data was analysed in PROC MIXED, PROC NLIN and PROC REG of SAS (version 9.4, SAS Institute Inc., Cary, NC, USA). There was no effect of diet on the in situ degradation parameters of the DDG (P > 0.050). However, for the diets, the readily soluble fraction (parameter "a") (P < 0.010), and the rate constant for degradation (parameter kd) of the potentially degradable fraction in the rumen (parameter “b”) (P = 0.050) of DM, decreased linearly. On the other hand, the parameter "b" (P < 0.01) and kd rate (P = 0.03) of NDF of the diets increased linearly. The in situ incubation time to estimate the in vivo DM digestibility ranged from 27.2-h to 37.7-h. For the NDF, the time was 60-h for all diets. In addition, to estimate the in vivo digestibility of DM (DMD), and the residual NDF (RNDF) of diets, two equations were suggested for each one: DMD = 804.8 - 0.092 × level, and DMD = 658 + 0.468 × a; RNDF = 393.9 - 0.138 × level, and RNDF = 874.3 - (0.602 × b) - (0.805 × I) + (1,662 × kd), where I = indigestible NDF. Therefore, the inclusion of low-fat DDG in finishing diets reduces performance, nutrient digestibility and energy intake. Keywords: Dried distillers grains. Finishing diet. Nellore.